Dropout Risk Factors in an Open and Distance Learning (ODL) Setting: A Case Study in Malaysia - Nora’ayu AHMAD UZIR; Muhammad Abdul Aziz NUR IZZUDDIN IZHAM; Nursalsabilla ANUAR; Irni Eliana KHAIRUDDIN; Muhammad Khairulnizam ZAINI (Communications of International Proceedings, 2023)
The growth of Open and Distance Learning (ODL) in tertiary education has led to an increased need for understanding the risks and challenges faced by students in order to promote student retention and success. However, as recent studies point out, and to the best of our knowledge, such research is still scarce. This study aims to explore the factors that contribute to the dropout risk, and to propose a novel framework to mitigate this risk in an ODL setting. Data was collected through semi-structured interviews with 15 former undergraduate students from various programs, disciplines, and levels of study. The interviews provided rich data of the underlying reasons associated with dropout, allowing for a comprehensive analysis of the issue. Purposive sampling was used to obtain personal experience, insights and perspectives on the factors that contribute to student attrition. In sum, the results suggest self-regulation is one of the important factors for academic success and persistence particularly in the context of online distance learning.
Keywords: Drop out; Open and Distance Learning; Higher Education